2014
DOI: 10.2196/resprot.3629
|View full text |Cite
|
Sign up to set email alerts
|

A Web-Based Training Program Using Cognitive Behavioral Therapy to Alleviate Psychological Distress Among Employees: Randomized Controlled Pilot Trial

Abstract: BackgroundA number of psychoeducational programs based on cognitive behavioral therapy (CBT) to alleviate psychological distress have been developed for implementation in clinical settings. However, while these programs are considered critical components of stress management education in a workplace setting, they are required to be brief and simple to implement, which can hinder development.ObjectiveThe intent of the study was to examine the effects of a brief training program based on CBT in alleviating psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Mori, Tajima, Kimura et al 22) delivered web-based CBT to employees (168 Japanese system engineers) experiencing distress. Participants received a 2.5-h group education CBT session in the workplace and 1 month of online CBT-based homework exercises.…”
Section: Resultsmentioning
confidence: 99%
“…Mori, Tajima, Kimura et al 22) delivered web-based CBT to employees (168 Japanese system engineers) experiencing distress. Participants received a 2.5-h group education CBT session in the workplace and 1 month of online CBT-based homework exercises.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we conducted a randomized controlled trial (RCT) to examine the effectiveness of one short session of management training to improve OJ for subordinates within private sector organizations. A previous RCT in occupational field found no significant effect on all-participant analysis but did detect significance in high-risk subgroup analysis 21 ) . However, two approaches have been proposed for educational intervention targeting whole populations versus high-risk groups, both of which are indispensable in the workplace 22 ) .…”
Section: Introductionmentioning
confidence: 81%
“…Another study examined the effects of a brief CBT-based training program in terms of alleviating psychological distress among employees and facilitating self-evaluation of stress management skills. This program combined group CBT education with web-based CBT homework, and led to a moderate alleviation of symptoms for employees with clinically significant psychological distress [ 17 ]. These reports suggested that Self-help CBT does appear to be a moderately effective intervention for a range of common mental health difficulties in the workplace.…”
Section: Introductionmentioning
confidence: 99%